Quality growth in poverty reduction Provinces in Indonesia - Kartini Saibeh; Wong Sing Yun (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
Poverty is still a major problem in Indonesia as reflected in the SDG's. This study aims to see how growth in Indonesia can reduce poverty. This study has a novelty in the research method that raises the issue of endogenous variables in the study. This study can have an impact on increasing valuable insights into the role of growth in decision-making, especially in cases of poverty. This study uses growth data as an independent variable, dependent variables consisting of poverty rates (P0), poverty depth rates (P1), poverty severity index, and other control variables that focus on data from all provinces in Indonesia from 2017-2023, utilizing quantitative analysis methods through the 2SLS (Two Stage Least Square) approach to overcome the issue of variable endogeneity. The results of the study explain that growth has a negative effect both by using the population index (P0), the Poverty Gap Index (P1), and the Poverty Severity Index (P2). so that this study is expected to be able to provide information to the government and policy makers to be able to focus on strategies that encourage regional economic growth.